Autoimmune manifestations in primary immunodeficiencies - M. I. Kaleda; I. P. Nikishina (Современная ревматология)
According to current understanding of the mechanisms underlying primary immunodeficiencies (PIDs) and their clinical course, there is a clear and clinically significant association between this group of disorders and autoimmune manifestations (AIMs).This article presents up-to-date information on AIMs in patients with PIDs, with a focus on the most common conditions and key clinical features that warrant consideration of PIDs in the differential diagnosis of patients with rheumatic diseases.